(untitled) (Journal of Informatics Education and Research, 2024)
In the contemporary organization development environment, the primary focus revolves around the performance of organizations, given the heightened awareness of customers regarding the services and overall environment they experience. The standing of an organization in the market is intricately linked to its productivity and the quality of its facilities andemployee motivation, especially in service industries like healthcare sector. The consensus acknowledges that the performance of an organization is profoundly shaped by the welfare policies and strategic decisions crafted by top management. Moreover, the motivation levels of employees to excel in their respective roles exert a substantial influence on the overall organizational performance. Over time, it has become evident that a capable leader in a prominent position within the organization plays a pivotal role in establishing the organization’s uniqueness, even amidst other influencing factors. This can be accomplished through employee motivation and welfare policies, which bear considerable significance, particularly in service industries. The forthcoming paper aims to evaluate theassess the degree of relationship between employee motivation and organization welfare policiesalong with the organizational performance, with a specific focus on hospitals in the Rajasthan with special case of Ajmer division.